Improved sacral neuromodulation in the treatment of the hyperactive detrusor: signal modification in an animal model - Seif, Christoph; Cherwon, Elly; Martínez y Portillo, Francisco-José; Alken, Peter; Jünemann, Klaus-Peter; Braun, Peter-Martin (BJU international, 2003)
OBJECTIVE To investigate different stimulation signals for the peripheral nerve evaluation test (PNE, carried out before implanting a sacral neuromodulator for functional voiding dysfunction) in an animal model and to determine their efficacy, as up to 80% of patients do not respond to the PNE test. MATERIALS AND METHODS PNE foramen electrodes were placed in the S3 of 12 anaesthetized Göttingen minipigs. First, detrusor instabilities were induced by the intravesical instillation of formalin. A 10-min stimulation phase with both a quasi-trapezoidal (QT) signal and a rectangular signal followed. An interval of 30 min elapsed between the series of stimulations. The attained bladder pressure values were registered on a urodynamic unit and evaluated as contractions and amplitudes per minute. Six minipigs were treated in the same way but were not stimulated and served as a control group. RESULTS After formalin instillation, the mean (sd) number of involuntary detrusor contractions was 3.5 (0.8)/min and the sum of amplitudes 7.2 (1.1) cmH2O/min. Subsequent NaCl instillation and QT-stimulation reduced the contractions to 0.3 (0.3)/min and the sum of amplitudes to 0.8 (0.4) cmH2O/min. Stimulation with a rectangular signal, as used in the PNE test, followed after an interval of 10 min, giving 1.1 (0.1) contractions/min and a sum of amplitudes of 5.1 (2.4) cmH2O/min. Within the control group there was no significant reduction. CONCLUSIONS These results show that QT-stimulation suppresses uncontrollable detrusor contractions in the minipig more effectively than the conventional rectangular stimulation presently applied in sacral neuromodulation.